Extended Range of Ultra Sparse Matrix Converter Using Integrated Switched Capacitor Network - Raghuram M.; Chauhan A.K.; Singh S.K. (My University, 2025)
Ultra sparse matrix converter (USMC) is known for ac-ac conversion with sinusoidal input currents, output voltages, and variable frequency operation. However, its operation is restricted for voltage gain up to 0.866 and load power factor angle up to 30° along with requirement of protection circuit for pulsating loads. This paper proposes switched capacitor USMC to overcome the restrictions of USMC with improved performance. Experimental results are provided to evaluate the converter capability and behavior under balanced and unbalanced input voltage conditions. Furthermore, the proposed converter is compared with the other counterparts. © 1972-2012 IEEE.